Information Systems Services Services Administration (Costumer Service) On Two Wheels Motor Vehicles Automotive Services By Using Visual Basic 6.0 and DatabaseMySQL - Muhammad Rizki Irwanto Oetomo (Jurnal Sistem Informasi, 2010)
In line with the rapid development of the era, the more problems faced by humans. The necessityto solve a problem quickly, accurately and efficiently is very necessary. Therefore science andinformation technology is always developed to make it happen. In this paper the author makes acomputerized system to process administrative services of two-wheeled motor vehicle servicingin the automotive service by using Visual Basic 6.0 programming language and MySQLdatabase. Programs that exist in this application, include a main menu menu displays the data,the transaction menu, the menu reports. Where there are data menu sub menu input customerdata, data goods, mechanical data and data types of service fees. Menu there are sub menutransaction transaction. While there are reports of sub menu print menu and save the receipts,customer data printing sub menu and sub menu print transaction data. Where is the menu of thisreport is used to display and print reports. The application of this system aims to replace themanual system with a system that has been computerized, with the hope to make way company'swork for the better, especially in the administration.